Jumpstarting Orange- Fleshed Sweetpotato in West Africa through Diversified Markets - Abidin, P.E.; Some, K.; Trucker, J.; Kiger, B.; Acheremu, K.; Amankwaah, V.A.; Amagloh, F.; Amoaful, E.F.; Njoku, J. (International Potato Center, 2015)
This flyer describes the objectives, activities, and progress made in implementing a three-year project that targets informal and formal orange-fleshed sweetpotato (OFSP) markets in Ghana, Nigeria and Burkina Faso between June 2014 and July 2015. The project is working towards four major outcomes at each target location: to establish commercial sweetpotato seed systems to provide clean planting material year round; to develop formal and informal markets for OFSP; to enable farmers including women, to participate in OFSP value chains; and to increase consumption of OFSP and other vitamin A-rich foods by vulnerable target populations, particularly women and children under the age of five.